VOICEXML-APPLICATIONS FOR E-COMMERCE AND E-LEARNING - Reusch, Peter J. A.; Stoll, Bastian; Studnik, Daniel; Swade, Joerg (International Journal of Computing, 2014)
VoiceXML is a language of the W3C to create voice-user interfaces, particularly for the telephone. It uses speech recognition and touchtone (DTMF keypad) for input, and pre-recorded audio and text-to-speech synthesis (TTS) for output. The text-to-speech synthesis feature of advanced VoiceXML tools like WebSphere opens new perspectives for e-commerce and e-learning. We are no longer restricted to pre-recorded audio but can bring any text to the ear of the user – a user that could be visually impaired and needs a voice channel to communicate – or a user who can read but who prefers to listen. VoiceXML-applications have been implemented by the authors to support e-commerce (selection of commodities from catalogues) and user guides for hardware (mobile phones, etc.) and software systems (MS project, etc.). New contributions to e-learning are offered.